Variations on some finite-dimensional fixed-point theorems - Mawhin, J. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We give rather elementary topological proofs of some generalizations of fixed-point theorems in R^n due to Pireddu-Zanolin and Zgliczynski, which are useful in various questions related to ordinary differential equations.